A combined physical and DEM modelling approach to improve performance of rotary dryers by modifying flights design. Issue 4 (15th February 2021) - Ghasemi, Alireza; Hasankhoei, Alireza; Parsapour, Gholamabbas; Razi, Erfan; Banisi, Samad
Abstract: To characterize the drying process in the Gol-E-Gohar pelletizing plant ball mill the material veiling profile (material showering) was studied by physical modeling and DEM. To simulate the trajectory of particles in the dryer in a reasonable period of time the GPU parallel processing was implemented in the DEM codes. After calibration of DEM parameters by using the model dryer, various flight designs were then employed in the simulation to find an appropriate veiling profile. It was found that by decreasing the release angle of flights from 70° to less than 40° the coverage of hot gas tunnel cross section by particles increases from 41.6% to 89.6%. The simulations also indicated that by changing the flight edge from the raised edge to the rectangular tooth-like type, the coverage of hot gas tunnel cross section could reach 97.1% and more uniform veiling profile could be obtained. Evaluation of the grinding performance over a period of 15 months showed an increase of 17 t/h in the throughput in the case of the new flights in mill No. 1 while for the same period, mill No.2 experienced a decrease of 7 t/h in the throughput with the original flights for the same feed.